Themis and Diké: the transversal relationship between justice and revenge in the case of federal congressman Paulo Salim Maluf - Gundim, Wagner (Revista da Faculdade de Direito do Sul de Minas, 2019)
The purpose of this article is to analyze whether there is a transverse relationship between the structures of revenge and justice, especially in the current law, based on the analysis of the case of Congressman Paulo Maluf, where there is a clear polarity on the possibility of granting custody due to his weakened health status. Initially, it points to the difficult conceptualization of justice and then to investigate the Greek mythological foundations that fall on the goddesses Themis and Diké, as a proposal to discover the birth of justice. Subsequently, it analyzes the structures of justice and revenge, comparing them. In the end, for the analysis not to be restricted to theory, it investigates the practical case related to the arrest of Congressman Paulo Salim Maluf to demonstrate that there is a transversal (and not diametrically opposed) relationship between the structures of justice and revenge.